2022
DOI: 10.1177/08862605221102483
|View full text |Cite
|
Sign up to set email alerts
|

Only “yes” means “yes”: Negotiation of Sex and Its Link With Sexual Violence

Abstract: Lack of consent is an essential characteristic of sexual violence. The present study was conducted to analyze the relation between sexual consent and the risk of perpetrating sexual aggression by men and victimization suffered by women in more depth. The sample consisted of 1681 heterosexual Spanish men and women aged 18–66 years. The participants completed an online survey containing the Spanish versions of the Sexual Consent Scale Revised and the Sexual Experiences Survey. The results showed that 70.2% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…The ambiguous communication of sexual intentions undermines perceptions and negotiations of consent, thereby creating a context that may promote sexual advances without ascertaining consent. 27,28 Several longitudinal studies have shown that sexual scripts for consensual sexual interactions which contain these risk factors prospectively predict both sexual aggression perpetration and sexual victimization [29][30][31][32] through their impact on sexual behavior that is congruent with the script.…”
Section: Sexual Scripts Sexual Behavior and Sexual Aggression Perpetr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ambiguous communication of sexual intentions undermines perceptions and negotiations of consent, thereby creating a context that may promote sexual advances without ascertaining consent. 27,28 Several longitudinal studies have shown that sexual scripts for consensual sexual interactions which contain these risk factors prospectively predict both sexual aggression perpetration and sexual victimization [29][30][31][32] through their impact on sexual behavior that is congruent with the script.…”
Section: Sexual Scripts Sexual Behavior and Sexual Aggression Perpetr...mentioning
confidence: 99%
“…The ambiguous communication of sexual intentions undermines perceptions and negotiations of consent, thereby creating a context that may promote sexual advances without ascertaining consent. 27,28…”
Section: Introductionmentioning
confidence: 99%
“…Esta movilización social visibilizó la injusticia testimonial que sufren las mujeres cuando denuncian que han sufrido violencia sexual, al no ser creídas en la mayoría de los casos cuando su relato no encaja en ciertos estereotipos de género (Alcoff, 2017; Medina, 2021;Rekers, 2022). También puso de manifiesto la escasa consideración social de la voluntad de las mujeres a la hora de mantener sexo, en particular, cuando prestan su consentimiento (Moyano et al, 2022).…”
Section: Contextualización De La Ley De Garantía Integral De La Liber...unclassified